2015
DOI: 10.3904/kjim.2015.30.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and non-immunologic complications of a third kidney transplantation

Abstract: Background/Aims:Patients who undergo repeat kidney transplantations (KTs) are considered at high risk for experiencing immunologic and non-immunologic complications. In this study, we investigated the clinical outcomes, including medical and surgical complications, of patients who underwent a third KT at our center.Methods:Between March 1969 and December 2012, a total of 2,110 KTs were performed at the Seoul St. Mary’s Hospital. Of them, we examined 11 patients who underwent a third KT, and investigated the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…Regarding the graft survival, our study presents a survival of 100% after 1 year and 74.1% after 5 years, respectively. These patient and graft survival rates of third graft recipients correlate with the results presented by almost all the recent studies [2,3,4,5,6,7,8,9]. …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Regarding the graft survival, our study presents a survival of 100% after 1 year and 74.1% after 5 years, respectively. These patient and graft survival rates of third graft recipients correlate with the results presented by almost all the recent studies [2,3,4,5,6,7,8,9]. …”
Section: Discussionsupporting
confidence: 77%
“…In the latest study by Kim et al [7], allograft survival rates for third graft recipients at 1 and 5 years of 81.8 and 42.9% were observed, respectively. Izquierdo et al [12] reported 92.7 and 90.6% patients and 88 and 76.4% graft survivals of third transplantation at 1 and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, a third kidney transplant procedure may be acceptable, although aggressive pretransplant immunomonitoring and patient selection may be required to reduce the risks of acute rejection and surgical complications. 25 Immunosuppression A 12-month single-arm pilot trial was carried out to evaluate efficacy and safety of sirolimus-tacrolimus in high-risk patients, including 28 patients who underwent retransplant versus a retrospective control group administered tacrolimus-mycophenolate mofetil (69 recipients). All patients were given basiliximab induction therapy.…”
Section: Immunologic Factorsmentioning
confidence: 99%